Potential Mechanisms of an Antiadenomyosis Chinese Herbal Formula Shaoyao-Gancao Decoction in Primary Cell Culture Model. (10th November 2014) - Guan, Yong-Ge; Liao, Jin-Bin; Li, Kun-Yin; Li, Yu-Cui; Song, Yang; Ling, Jing; Su, Zi-Ren
Abstract : Background . Shaoyao-Gancao Decoction (SGD), a well-known traditional Chinese medicine prescription, has been widely used to treat adenomyosis, dysmenorrhea, abdominal pain, and inflammation in Asia. However, the mechanism underlying the effectiveness of SGD in the treatment of adenomyosis still remains elusive. The present study aimed to investigate the bioactivity of SGD and its underlying molecular mechanisms using cultured human adenomyosis-derived cells. Methods . Human adenomyosis-derived cells were treated with SGD and its major constituents (paeoniflorin and liquiritin) in vitro . Effects of SGD, paeoniflorin, and liquiritin on cell proliferation and apoptosis were examined by MTT assay and flow cytometry analyses. The effects of SGD, paeoniflorin, and liquiritin on the production of PGE2 and PGF2 α were assayed using ELISA. ER- α and OTR mRNA expression levels were also evaluated by real-time qRT-PCR. Results . SGD, paeoniflorin, and liquiritin inhibited proliferation and induced apoptosis of human adenomyosis-derived cells in a dose-dependent manner. SGD and paeoniflorin significantly reduced the PGE2 and PGF2 α production. Furthermore, they remarkably decreased the mRNA levels of ER- α and OTR. Conclusions . The results of this study provide possible mechanisms for the bioactivity of SGD for treating adenomyosis and contribute to the ethnopharmacological knowledge about this prescription.